How Crime has Changed in a Universally Mobile Society, Based on the Example of Poland. A Research Concept (Contemporary Central & East European Law, 2020)
We live in a time of constant change. For modern societies, the period of the last 30 years is also a time of changes connected with the reconstruction of the surrounding reality. For Poland, it is also a period of changes in the political and economic systems. Such profound changes must also be followed by changes in the structure of crime. Technological changes and the mobility of societies are changing not only the methods but also the ways in which crimes are committed. New types of crime are emerging, while ‘old crimes’ are changing or disappearing. The aim of this article is to outline the above issues within the context of a planned research project on the analysis of changes in crime, using the example of Poland.